SOSIALISASI INSEMNISASI BUATAN (IB) PADA TERNAK BABI DI DESA TUMORI - FATOLOSA HULU; JELISWAN BERKAT IMAN JAYA GEA; AGUSMAN NIAT BERKAT ZEBUA; FALESTINA LASE; LISNA WITA; NURMESERI CORDIAS AGUNG BIDAYA; LENI PUTRI MAWATI WARUWU; YERILIA WARUWU; DORKAS FEBRIYANTI ZENDRATO; LUCKY GOOD SPEACK WARUWU; OKTAVIANUS NDRURU; OBINI WAHYUAN ZEGA; RENCANA HALAWA; YUNISA HALAWA; YUPI IMAN BERKAT GULO; YUSMAN LAIA; ALEXSANDER TAFONAO (LPPI UMN AL WASHLIYAH, 2026)
This study aims to evaluate the success and impact of implementing Artificial Insemination (AI) technology on the reproductive efficiency and productivity of pigs i Tumori Village. The research employed survey and case study methods, monitoring the reproductive progress of sows bred via AI. Measured parameters included conception rate, litter size, and efficiency regarding time and cost compared to natural mating. The results indicate that the adoption of AI among pig farmers in Tumori Village remains low; the community still predominantly relies on natural mating methods, despite the fact that AI aims to enhance reproductive efficiency and the income potential of local pig farmers.